2008
DOI: 10.1080/17538150802127207
|View full text |Cite
|
Sign up to set email alerts
|

Design and development process of patient-centered computer-based support system for patients with schizophrenia spectrum psychosis

Abstract: The effectiveness needs to be evaluated carefully in future clinical trials. This will offer valuable information for policymakers, organizations and health care practitioners about the usability of web-based patient education in the area of mental health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 44 publications
0
50
0
Order By: Relevance
“…Acceptability, usability and safety of online and mobile-based interventions 3.1.1. Web-based psycho-education and CBT Three pilot studies provided data on the usability and acceptability of web-based psycho-education (Valimaki et al, 2008;Anttila et al, 2012) and interactive CBT (Gottlieb et al, 2013) for patients with chronic schizophrenia delivered in hospital-based settings (Table 1). Overall patients considered the web-based interventions to be usable (Valimaki et al, 2008) and helpful (Gottlieb et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Acceptability, usability and safety of online and mobile-based interventions 3.1.1. Web-based psycho-education and CBT Three pilot studies provided data on the usability and acceptability of web-based psycho-education (Valimaki et al, 2008;Anttila et al, 2012) and interactive CBT (Gottlieb et al, 2013) for patients with chronic schizophrenia delivered in hospital-based settings (Table 1). Overall patients considered the web-based interventions to be usable (Valimaki et al, 2008) and helpful (Gottlieb et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Web-based psycho-education and CBT Three pilot studies provided data on the usability and acceptability of web-based psycho-education (Valimaki et al, 2008;Anttila et al, 2012) and interactive CBT (Gottlieb et al, 2013) for patients with chronic schizophrenia delivered in hospital-based settings (Table 1). Overall patients considered the web-based interventions to be usable (Valimaki et al, 2008) and helpful (Gottlieb et al, 2013). One study reported that 73 (79%) patients attended all 6 programmed psychoeducation sessions, with 69 (74%) successfully completing the set tasks (Anttila et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations